2013
DOI: 10.1152/ajpendo.00380.2013
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle denervation causes skeletal muscle atrophy through a pathway that involves both Gadd45a and HDAC4

Abstract: Bongers KS, Fox DK, Ebert SM, Kunkel SD, Dyle MC, Bullard SA, Dierdorff JM, Adams CM. Skeletal muscle denervation causes skeletal muscle atrophy through a pathway that involves both Gadd45a and HDAC4. Am J Physiol Endocrinol Metab 305: E907-E915, 2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 32 publications
4
111
1
1
Order By: Relevance
“…We have shown previously, that mice lacking SOD1 showed significant increase in AChR alpha mRNA levels indicating the denervation process (Jang and Van Remmen, 2011). Along with AChR mRNA, we investigated the levels of Runx1 (Wang et al, 2005), MyoD (Ishido et al, 2004) and Gadd45a (Bongers et al, 2013) and found that compared with wild-type/Sham mice, G93A/Sham mice showed several fold increases in AChR alpha, Runx1, MyoD and GADD45a mRNA levels (Figure 5 A, B, C, D) as would be expected. G93A mice who experienced a mild TBI showed further increases in these denervation markers, which were significant with AChR and Runx1 mRNA levels.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We have shown previously, that mice lacking SOD1 showed significant increase in AChR alpha mRNA levels indicating the denervation process (Jang and Van Remmen, 2011). Along with AChR mRNA, we investigated the levels of Runx1 (Wang et al, 2005), MyoD (Ishido et al, 2004) and Gadd45a (Bongers et al, 2013) and found that compared with wild-type/Sham mice, G93A/Sham mice showed several fold increases in AChR alpha, Runx1, MyoD and GADD45a mRNA levels (Figure 5 A, B, C, D) as would be expected. G93A mice who experienced a mild TBI showed further increases in these denervation markers, which were significant with AChR and Runx1 mRNA levels.…”
Section: Discussionsupporting
confidence: 59%
“…We investigated, in the gastrocnemius muscle, AChR mRNA (Jang and Van Remmen, 2011), as well as the levels of other denervation markers Runx1 (Wang et al, 2005), MyoD (Ishido et al, 2004) and Gadd45a (Bongers et al, 2013). One month after TBI compared with WT sham mice, G93A sham mice showed a several fold increase in AChR alpha, Runx1, MyoD and GADD45a mRNA levels (Figure 5 A, B, C, D) indicating denervation in the gastrocnemius muscle of these mice.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of eMHC expression in old muscle treated with butyrate suggests that butyrate prevents denervation or that butyrate prevents the formation of new fibers. Furthermore, butyrate prevented the age‐related increase in Gadd45a expression, a gene that mediates denervation‐induced muscle trophy that is directly regulated by HDAC4 (Bongers et al ., 2013), and central nuclei in muscle fibers, suggesting butyrate prevents degeneration of muscle fibers. Conversely, HDAC4, AChRα, and Runx1 were increased in both control and butyrate‐treated groups, while NCAM was not affected by age or diet.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently, we found that increased ATF4 expression is sufficient to induce skeletal muscle fiber atrophy (18), and ATF4 is required for skeletal muscle atrophy in some but not all contexts. For example, ATF4 is required for skeletal muscle atrophy caused by fasting or aging (18,19), but it is not required for muscle atrophy caused by muscle denervation (7). To test the hypothesis that ATF4 might be required for immobilization-induced skeletal muscle atrophy, we generated and studied muscle-specific ATF4 knockout (ATF4 mKO) mice, which lack ATF4 in skeletal muscle fibers from birth but develop normally and exhibit no apparent phenotype under basal conditions (17).…”
Section: Insights Into Disuse Muscle Atrophy Using Systems Approachesmentioning
confidence: 99%